Un sistema de gestión en control y seguridad industrial para el área de producción y almacenamiento de una empresa recicladora de plásticos, en la ciudad de Guayaquil - Cáceres Del Pezo, Ana Paola (2009)
Industrial Safety over time has evolved, albeit slowly, because many companies have resisted change, some people still have not become awared of how important it is for the company to take care of health and safety of its employees and are bent by old ideas, based on early measures concerning the regulation of the risks involved in carrying out work activities. Therefore, the organization has decided to be part of the evolution and allow us to design a System of Control and Industrial Safety, the same that will identify and assess risks associated with the work performed, and so to conduct their activities safely. It should be noted that once the system design, it can be implemented by the company. The Company believes that the design and implementation of a management system in industrial control and security will help prevent economic losses and human insecurity that could generate. It recognizes that this represents an investment because their benefits is to prevent accidents and all direct and indirect costs that they entail.